Differences in teratogenicity of some vitamin K antagonist substances used as human therapeutic or rodenticide are due to major differences in their fate after an oral administration. (15th October 2020) - Chetot, Thomas; Mouette-Bonnet, Marjorie; Taufana, Shira; Fourel, Isabelle; Lefebvre, Sebastien; Benoit, Etienne; Lattard, Virginie
Highlights: Bromadiolone, an antivitamin K rodenticide does not exhibit the teratogenic effect of warfarin, an antivitamin K drug. Warfarin is highly transferred from the dam to the fetus during gestation. There is little or no transfer of bromadiolone from the dam to the fetus during gestation. This difference appears to be due to almost complete uptake of bromadiolone by the dam's liver resulting in its low bioavailability in dam's plasma. Abstract: All vitamin K antagonist active substances used as rodenticides were reclassified in 2016 by the European authorities as active substances "toxic for reproduction", using a "read-across" alternative method based on warfarin, a human vitamin K antagonist drug. Recent study suggested that all vitamin K antagonist active substances are not all teratogenic. Using a neonatal exposure protocol, warfarin evokes skeletal deformities in rats, while bromadiolone, a widely used second-generation anticoagulant rodenticide, failed to cause such effects. Herein, using a rat model we investigated the mechanisms that may explain teratogenicity differences between warfarin and bromadiolone, despite their similar vitamin K antagonist mechanism of action. This study also included coumatetralyl, a first-generation active substance rodenticide. Pharmacokinetic studies were conducted in rats to evaluate a potential difference in the transfer of vitamin K antagonists from mother to fetus. The data clearly demonstrate that warfarin is highly transferred from the mother to the fetus during gestation or lactation. In contrast, bromadiolone transfer from dam to the fetus is modest (5% compared to warfarin). This difference appears to be associated to almost complete uptake of bromadiolone by mother's liver, resulting in very low exposure in plasma and eventually in other peripheric tissues. This study suggests that the pharmacokinetic properties of vitamin K antagonists are not identical and could challenge the classification of such active substances as "toxic for reproduction".